Exploring Waqf Management Transformation: Opportunities and Challenges (Case Study in Ismuhu Yahya Foundation Pontianak) - Hatimah , Husnul; Sukoharsono, Eko Ganis; Djamhuri , Ali; Adib, Noval (Journal of Ecohumanism, 2024)
This study aims to explore the impact of technology implementation on the efficiency of waqf management in the non-profit organization Ismuhu Yahya Foundation Pontianak. Currently, waqf is undergoing a transformation as a result of advances in digital technology. As one of the important social and humanitarian services, an in-depth understanding of the adaptation process is needed to make this digital transformation work. This research uses a qualitative approach with a case study method to explore the impact of waqf management transformation, as well as to understand the ongoing digitalization process. Through interviews, direct observation, and review of relevant documents, this research explores the changes that occurred in waqf management at Ismuhu Yahya Foundation Pontianak. The results show a significant improvement in the efficiency of waqf management, including administrative cost savings and increased transparency. In addition, this research provides some novelty and unique contributions. First, by raising the topic of digital transformation in waqf management, which has not been widely studied, this research brings novelty by introducing a theme that is relevant to current technological developments. Secondly, as an in-depth local case study, the selection of Ismuhu Yahya Foundation provides new value as not many researchers have explored local areas with a qualitative approach. Third, the specific opportunities and challenges faced during the transformation process. Fourth, this study also found changes in the interaction between waqif (waqf giver) and nazir (waqf recipient). Finally, this study can contribute to the development of theories on waqf management, particularly in the context of digital transformation, which can serve as a foundation for future research and implementation.